Effects of empagliflozin on cardiovascular and renal outcomes in heart failure with reduced ejection fraction according to age: a secondary analysis of EMPEROR-Reduced - Filippatos, Gerasimos; Anker, Stefan D.; Butler, Javed; Farmakis, Dimitrios; Ferreira, João Pedro; Gollop, Nicholas D.; Brückmann, Martina; Iwata, Tomoko; Pocock, Stuart; Zannad, Faiez; Packer, Milton (European journal of heart failure, 2022)
Aims Empagliflozin improves cardiovascular and renal outcomes in patients with heart failure (HF) and reduced ejection fraction (HFrEF), but its efficacy and safety across patient's age is not well established. Methods and results We assessed the effects of empagliflozin (10 mg daily) versus placebo, on top of standard HF therapy, in symptomatic HFrEF patients with a left ventricular ejection fraction ≤40% and increased natriuretic peptides stratified by age (<65, 65-74, ≥75 years). The primary endpoint was a composite of cardiovascular death or HF hospitalization. Key secondary endpoints included first and recurrent HF hospitalizations and slope of change in estimated glomerular filtration rate (eGFR); the latter was supported by an analysis of a renal composite endpoint (chronic dialysis or renal transplantation or profound and sustained reduction in eGFR). Of 3730 patients, 38% were <65 years, 35% were 65-74 years and 27% were ≥75 years. Compared with placebo, empagliflozin reduced the primary endpoint consistently across the three age groups (hazard ratio 0.71 [95% confidence interval 0.57-0.89] for <65 years, 0.72 [0.57-0.93] for 65-74 years, 0.86 [0.67-1.10] for ≥75 years, interaction p-trend test = 0.24). The effects of empagliflozin were also consistent across age groups for key secondary endpoints of first and recurrent HF hospitalization (p-trend = 0.30), the rate of decline in eGFR (p-trend = 0.78) and the renal composite (p-trend = 0.94). Adverse events (AEs), serious AEs and AEs leading to drug discontinuation increased with age in both treatment arms, but empagliflozin did not increase their incidence over placebo within each age group. Conclusion The efficacy and safety of empagliflozin in improving cardiovascular and renal outcomes in HFrEF was consistent across the spectrum of age, including older patients (aged ≥75).
Erstmals veröffentlicht: 04. Oktober 2022
Gesehen am 18.06.2024